The Genetic Risk for COVID-19 Severity Is Associated With Defective Immune Responses - Kuijpers, Yunus; Chu, Xiaojing; Jaeger, Martin; Moorlag, Simone J. C. F. M.; Koeken, Valerie A. C. M.; Zhang, Bowen; Nooijer, Aline de; Grondman, Inge; Gupta, Manoj Kumar; Janssen, Nico; Mourits, Vera P.; de Bree, L. Charlotte J.; et al. (Frontiers in Immunology, 2022)
Recent genome-wide association studies (GWASs) of COVID-19 patients of European ancestry have identified genetic loci significantly associated with disease severity. Here, we employed the detailed clinical, immunological and multi-omics dataset of the Human Functional Genomics Project (HFGP) to explore the physiological significance of the host genetic variants that influence susceptibility to severe COVID-19. A genomics investigation intersected with functional characterization of individuals with high genetic risk for severe COVID-19 susceptibility identified several major patterns: i. a large impact of genetically determined innate immune responses in COVID-19, with ii. increased susceptibility for severe disease in individuals with defective cytokine production; iii. genetic susceptibility related to ABO blood groups is probably mediated through the von Willebrand factor (VWF) and endothelial dysfunction. We further validated these identified associations at transcript and protein levels by using independent disease cohorts. These insights allow a physiological understanding of genetic susceptibility to severe COVID-19, and indicate pathways that could be targeted for prevention and therapy.